Silicon in action: Between iron scarcity and excess copper - Nikolić, Dragana; Bosnić, Dragana; Samardžić, Jelena (Frontiers in Plant Science, 2023)
Essential micronutrients belonging to the transition metals, such as Fe and Cu, are indispensable for plant growth and stress tolerance; however, when present in excess, they can become potentially dangerous producers of reactive oxygen species. Therefore, their homeostases must be strictly regulated. Both microelement deficiencies and elevated concentrations of heavy metals in the soil are global problems that reduce the nutritional value of crops and seriously affect human health. Silicon, a beneficial element known for its protective properties, has been reported to alleviate the symptoms of Cu toxicity and Fe deficiency stress in plants; however, we are still far from a comprehensive understanding of the underlying molecular mechanisms. Although Si-mediated mitigation of these stresses has been clearly demonstrated for some species, the effects of Si vary depending on plant species, growing conditions and experimental design. In this review, the proposed mechanistic models explaining the effect of Si are summarized and discussed. Iron and copper compete for the common metal transporters and share the same transport routes, hence, inadequate concentration of one element leads to disturbances of another. Silicon is reported to beneficially influence not only the distribution of the element supplied below or above the optimal concentration, but also the distribution of other microelements, as well as their molar ratios. The influence of Si on Cu immobilization and retention in the root, as well as Si-induced Fe remobilization from the source to the sink organs are of vital importance. The changes in cellular Cu and Fe localization are considered to play a crucial role in restoring homeostasis of these microelements. Silicon has been shown to stimulate the accumulation of metal chelators involved in both the mobilization of deficient elements and scavenging excess heavy metals. Research into the mechanisms of the ameliorative effects of Si is valuable for reducing mineral stress in plants and improving the nutritional value of crops. This review aims to provide a thorough and critical overview of the current state of knowledge in this field and to discuss discrepancies in the observed effects of Si and different views on its mode of action.